Quinidine Therapy for Lennox-Gastaut Syndrome With KCNT1 Mutation. A Case Report and Literature Review - Jia, Yu; Lin, Yicong; Li, Jing; Li, Mingyu; Zhang, Yifan; Hou, Yue; Liu, Aihua; Zhang, Liping; Li, Liping; Xiang, Peng; Ye, Jing; Huang, Zhaoyang; et al. (Frontiers in Neurology, 2019)
Mutations in the Potassium channel subfamily T member 1 (KCNT1) gene have been reported in a range of epileptic encephalopathies. Here we report a case of a 12-year-old male suffering from multiple types of epileptic seizures and cognitive decline from the age of 10. The patient had four types of epileptic seizures, including tonic seizures, atypical absence seizures, myoclonic seizures and generalized tonic-clonic seizures. And the electroencephalogram showed generalized slow spike-and-slow-waves, mutiple-spike-and-slow-waves as well as short-term fast rhythms bursts. Thus, he was diagnosed as Lennox-Gastaut syndrome. The patient had failed to control seizures after using five first-line antiepileptic drugs. Whole exome sequencing revealed a missense KCNT1 mutation (c.625 C>T). Previous studies revealed that quinidine could block KCNT1 channel. Therefore, we assumed that quinidine might be effective for him. Add-on treatment with quinidine was started when the patient was 12 years old. After an 8-month treatment, the frequency of seizures and epileptiform discharges were significantly reduced. In conclusion, quinidine therapy may offer a new choice for the treatment of Lennox-Gastaut syndrome with KCNT1 mutations.